Courage And Self-Defense Reflected In Suzanne Collins's The Hunger Games Novel (2008): A Psychoanalytic Approach - Mehendra, Indra Ajie Listya, Dr. Phil. Dewi Candraningrum, M.Ed, Nur Hidayat, M.Pd (2014)
This study is strived to show courage and self-defense which is represented by the main character. This research delves into how courage and self-defense have some bearing on personality of the main character. The Hunger Games novel is analyzed by using a psychoanalytic approach, it is done by ascertaining and determining two object: the first is analyzing the novel based on its structural elements and based on the psychoanalytic approach. This research is descriptive qualitative research. In this method, there are two types of data source, namely primary and secondary data source. The primary data source is The Hunger Games novel written by Suzzane Collins. Meanwhile, the secondary data source are other materials taken from books, journals, and internet related to the study. Both of data are collected through library research and analyzed by descriptive analysis. Based on the analysis, the researcher pulls the following conclusions. First, based on the structural analysis of each statement, it reveals that the character and characterization, setting, plot, point of view, and theme are correlated to each other and mold a unity of delightful, enjoyable, smashing novel. Second, based on the psychoanalytic approach, the analysis puts on view that the personality of the main character is influenced by three domains of mind, they are id, ego, and superego.